A synthetic biology approach for the transformation of l-α-amino acids to the corresponding enantiopure (R)- or (S)-α-hydroxy acids. Issue 14 (9th January 2015) - Gourinchas, Geoffrey; Busto, Eduardo; Killinger, Manuela; Richter, Nina; Wiltschi, Birgit; Kroutil, Wolfgang
Abstract : A synthetic biology approach enabled the design of a single E. coli cell catalyst co-expressing three enzymes (l -AAD, l - or d -HIC and FDH) for the quantitatively transformation of l -amino acids to the corresponding optically pure ( R )- and ( S )-α-hydroxy acids. Abstract : Combinatorial assembly and variation of promoters on a single expression plasmid allowed the balance of the catalytic steps of a three enzyme (l -AAD, HIC, FDH) cascade in E. coli . The designer cell catalyst quantitatively transformed l -amino acids to the corresponding optically pure ( R )- and ( S )-α-hydroxy acids at up to 200 mM substrate concentration.